Microsoft Office 2000 - Morrison, Connie (South-Western Computer Education, 2001)
Cover all of the basics with this new Microsoft Office 2000 book! As part of our new BASICS series, it is ideal for lower-level users of the new Microsoft Office 2000 integrated software. Though introductory in nature, the book comprehensively covers the most popular features of word processing, spreadsheets, databases, and much more